Kualitas Produk, Harga Terhadap Loyalitas Dan Kepuasan Konsumen Sebagai Variabel Intervening Pengguna Tokopedia Di Kabupaten Gresik - Muhammad Rosyihuddin (Jurnal Manajerial, 2020)
Purpose - to find out the extent of satisfaction and the level of loyalty of consumers who have shopped at Tokopedia. Design / Methodology / Approach - In this study, there are two factors that become indifferent for researchers to make reference to independent variables, namely product quality and price. The location of research in Gresik Regency, the number of respondents numbered 100 respondents using purposive sampling method with the provisions of respondents who have made repeated purchases at Tokopedia. The results of this study were analyzed by path analysis and must go through instrument testing, classical assumptions, and then proof of the research hypothesis. Results and Discussion - Based on the results of research that product quality and price have a direct effect on customer satisfaction and customer satisfaction, product quality and price have a direct effect on loyalty to Tokopedia users in Gresik Regency. While product quality and price have an indirect effect on loyalty through consumer satisfaction of Tokopedia users in Gresik Regency. These results prove that product quality has a smaller coefficient on satisfaction and loyalty than the price variable. Consumer satisfaction and loyalty have a significant effect compared to other variables. Testing the path analysis proves that product quality and price affect indirectly on loyalty through satisfaction, but based on the findings the coefficient value of total product quality is smaller than the price variable. Conclusion - Based on the results of the study prove that all hypotheses can be accepted (product quality, price, product quality directly and indirectly affect customer satisfaction and loyalty). Research Implications - it is hoped that the results of this study can add insight to businesses in the field of online business, to pay attention to the quality of products, prices, to foster customer loyalty and satisfaction.